Kepemimpinan Pendidikan dan Manajemen Mutu Terpadu: Tinjauan atas Strategi Peningkatan Kualitas Sekolah di Era Global (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Educational quality is a strategic issue that plays a crucial role in determining the competitiveness of human resources in the global era. The main factors influencing its achievement include effective leadership and the implementation of Total Quality Management (TQM). However, previous studies reveal diverse approaches and findings that require a more comprehensive synthesis. Therefore, this article aims to systematically examine the role of leadership and quality management strategies in improving educational quality and to address the following questions: (1) how leadership contributes to the improvement of educational quality, and (2) how quality management strategies can be implemented to address global challenges. The method employed is a literature review through a systematic search of articles using Google Scholar and Publish or Perish (PoP). The keywords “conflict resolution” and “quality leadership” were used to identify relevant literature. Out of 50 articles identified, 19 articles were selected based on publication year criteria (2022–2025), open-access availability, and topic relevance. The selected articles were then coded and categorized into thematic groups. The main findings reveal three dominant patterns: (1) visionary, transformational, and authentic leadership significantly influence educational quality; (2) TQM strategies serve as an innovative framework for quality improvement; and (3) a quality-oriented culture is essential in addressing global challenges. In conclusion, this synthesis emphasizes the importance of quality-based leadership and provides directions for future research related to the implementation of TQM in the digital era.